Analysis and Design of Multicarrier Modulation Protocols in Cognitive Radios - Ravinder Kumar, P.; Narayandas, Vikram; Leelavathi, P.; V. M. Sandeep (Asian Journal of Electrical Sciences, 2012)
In this paper new techniques that deal with the issue of spectrum management have to be developed. It is possible to increase the spectral efficiency by either shifting carrier frequencies closer together or altering the roll off factor .The second approach does not seems to be efficient than the first, due to increase in bandwidth, which leads to increase in noise, interference, multipath fading The first concept is able to control the Guard band dynamically. Possibilities to reduce the guard band between successive channels dynamically are to beinvestigated, thus improving spectral efficiency. This can be done efficiently by Multicarrier modulation Multicarrier modulation which has an ability to increase in the data rates and simultaneously we can decrease in the interference due to multipath fading channels. Multicarrier modulation schemes are of two types namely, Non-contiguous orthogonal frequency division multiplexing and Non-contiguous non orthogonal frequency division multiplexing. The proposed paper aims to investigate the various features of Multicarrier, Multipath system to address the challenges in wireless communications and provide a solution for the optimum utilization of the resources.